PGI score: prospective validation and correlation with SOFA, SAPS-II, and APACHE-II scores for predicting outcomes in acute aluminum phosphide poisoning. Issue 2 (1st April 2022) - Pannu, A K; Jhuria, L; Bhalla, A; Sharma, N
Abstract: Introduction: We recently derived a simplified 3-point PGI score (representing blood pH < 7.25, Glasgow coma scale [GCS] score < 13, and impaired systolic blood pressure [SBP] < 90 mm Hg), which accurately predicted in-hospital case fatality ratio (CFR) in acute aluminum phosphide poisoning. The present study aimed to validate the PGI score and compare it with Acute Physiologic Assessment and Chronic Health Evaluation (APACHE) II score, Sequential Organ Failure Assessment score (SOFA), and Simplified Acute Physiology Score (SAPS) II scores. Patients and Methods: We performed a prospective cohort study in adult patients with aluminum phosphide ingestion admitted in PGIMER, Chandigarh (India), from April 2013 to August 2014. A univariant analysis detected the association of various baseline variables with CFR. Correlation of the PGI score with SOFA, SAPS-II, and APACHE-II scores was performed using Spearman's correlation ( rs, range −1 to +1) and scatter plots. Results: Seventy-six patients were enrolled (mean age, 28.3 years; 41 males). CFR was 60.5%. PGI score variables—pH, GCS, and impaired SBP predicted CFR ( P -value <0.001). Among patients with a total PGI score of 3 or 2, 100% died, compared with 50% in score 1 and 10.7% in score 0. Baseline PGI, SOFA, SAPS-II, and APACHE-II scores predicted CFR ( P -value <0.001). There was a positive correlation between the PGI score and SOFA score ( rs, 0.855), SAPS-II score ( rs, 0.861), and APACHE-II score ( rs, 0.883). The P -value for all rs values was <0.001. Conclusion: The PGI score is a validated toxidrome-specific and simplified risk-stratification tool. Validation in other populations is warranted to confirm its routine use.